2022
DOI: 10.3390/ceramics5040050
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrical Properties of Carbon-Rich Polymer Derived Silicon Carbonitride (SiCN)

Abstract: This article reports on the structure and electronic properties of carbon-rich polysilazane polymer-derived silicon carbonitride (C/SiCN) corresponding to pyrolysis temperatures between 1100 and 1600 °C in an argon atmosphere. Raman spectroscopy, X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), Scanning Electron Microscopy (SEM) and Hall measurements were used to support the structural and electronic properties characterization of the prepared C/SiCN nanocomposites. A structural analysis us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…It was found that the electrical conductivity increases with the amount of DVB and the results were between 0.1 and 1.2 S/cm. This outcome is comparable with the amorphous carbon-rich C/SiCN nanocomposites prepared by Adigun et al [56]. As well known from the literature, pure OPSZ samples are insulators at pyrolyzing temperature below 1000 • C [1,15].…”
Section: Samplesupporting
confidence: 87%
“…It was found that the electrical conductivity increases with the amount of DVB and the results were between 0.1 and 1.2 S/cm. This outcome is comparable with the amorphous carbon-rich C/SiCN nanocomposites prepared by Adigun et al [56]. As well known from the literature, pure OPSZ samples are insulators at pyrolyzing temperature below 1000 • C [1,15].…”
Section: Samplesupporting
confidence: 87%
“…Therefore, the resulting diffraction patterns only resembled SiC. Specifically, only 3C‐SiC, as established research states, is preferred under most synthetic conditions, including the decomposition of PSZ polymers 16,26 . The hexagonal type of diffraction peaks corresponds to SFs near the (1 1 1) planes centered at 35.6° (2 θ ).…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, only 3C-SiC, as established research states, is preferred under most synthetic conditions, including the decomposition of PSZ polymers. 16,26 The hexagonal type of diffraction peaks corresponds to SFs near the (1 1 1) planes centered at 35.6 • (2θ). These SF peaks consist of growth faults (twin faults) and intrinsic and extrinsic deformation faults.…”
Section: Xrdmentioning
confidence: 99%
“…The 2D band observed around 2700 cm −1 is usually found in defect free graphite samples while the D + G band is assigned to the disordered state of the carbon nanostructure in the samples (Gao et al 2012 ; Colombo et al 2010 ; Wen et al 2020 ; Adigun et al 2022 ). At close observation, this amorphous state decreases as the coal wastes transform into carbon/ceramic composites.…”
Section: Resultsmentioning
confidence: 99%